Morphology And Morphometry of Human External Ear with Its Significance in Sex Determination and Stature Estimation - An Observational Study [version 2; peer review: 1 approved, 2 approved with reservations, 1 not approved] - Acharya, Shwetha; Gupta, Chandni; Palimar, Vikram; Guruprasad Kalthur, Sneha; Adhikari, Purnima (F1000 research, 2025)
Background The human ear is unique to individuals, and ear prints, like fingerprints, are discrete enough to distinguish identical twins. Therefore, the external ear could be used to identify both living and deceased individuals. Therefore, this study aimed to evaluate the stature and sexual dimorphism of the external ear using various morphometric parameters and morphological features for forensic identification. Methods This study included 40 participants (20 males and 20 females). Participants were between the age of 18-25yrs. Measurements were taken with the subject's head in the Frankfort horizontal plane. 18 measurements were taken like ear length and width, lobule height and width, concha length and width, tragus length, morphological ear length, helical mastoid distal length, thickness of ear lobe, auricular inclination angle, antihelical take off angle, concha mastoid angle, auricular index, lobular index, concha index, ear attachment length index and conchal bowl depth on external ear were taken and the morphological features like shape of ear, ear lobe, darwin's tubercle and ear tragus, attachment of ear lobe and form of helix of both the right and left ears were noted. A digital Vernier caliper was used to measure all parameters. The angles were measured using a goniometer. Normal distribution was verified using the Shapiro-Wilk test. For normally distributed parameters, an independent t-test was used, and for non-normally distributed parameters, the Mann-Whitney U test was used to compare sexes. To compare the right and left parameters, independent t-tests (for normally distributed data) and Mann-Whitney U tests (for non-normally distributed data) were applied. Sex determination and stature estimation were performed using logistic regression analysis. Results In males and females, the most common shape was oval, and the ear lobe was free. The most common shape of the ear lobe in males was arched, while in females, it was triangular. In males and females, the most common form of the helix was the concave marginal. In males, the most common shape of the tragus was round, whereas in females, it was long. In males and females, the most common shape of Darwin's tubercle was enlarged. It was seen that the right lobe width showed perfect separation, indicating its potential as an extremely reliable predictor. It was noted that in females, the strongest correlation with height was with the ear inclination angle on both sides. Conclusion The results of this study can help forensic anthropologists identify the sex and stature of a person from various ear measurements.